A 3000 year high resolution multi-proxy record of environmental change from lake Gripdeild, eastern Iceland - Halldóra Björk Bergþórsdóttir 1987- (2014)
A high-resolution sediment core from Gripdeild, a lake located in eastern Iceland, provides a record of environmental change over at least the last 3ka. The sediment core contains numerous tephra layers of known age that can provide an age model and allow correlation with other well-dated lacustrine sediment records from Iceland. A number of environmental proxies used to reconstruct the environmental change includes δ13C, δ15N, TOC, TN, MS, density and C:N. Principal Component Analysis (PCA) was used to identify the strongest proxies measured. The proxies indicate that cooling associated with Neoglaciation had already set in before 3 ka. This is most apparent in the consistent rise of sediment accumulation rate and C:N ratios throughout the record interpreted as increased landscape instability and soil erosion associated with cooler summers. The combined 3 ka proxy record and the result from the PCA is used to describe oscillation between contrasting conditions; one reflecting landscape instability indicating cooler conditions, the other reflecting higher stability indicating warmer times. This combined multi-proxy record of the late Holocene environmental conditions at Gripdeild suggests stepwise changes during the last 3 ka that can be subdivided into three main intervals: The first stage covering the interval between 1000 BC and 500 AD is characterized by a slight increase in landscape instability and suppressed primary production, possibly related to unfavorable growing conditions. The second stage between 500 and 1250 AD is characterized by increased variations in the organic matter proxies indicating more fluctuating conditions than before, but the higher values of ∂13C and TOC that anti-correlate with ∂15N and C:N between ca. 900 and 1100 AD could possibly reflect short, warmer times referred to as the Medieval Warm Period. The third stage covers the time between 1250 to present, representing a time of large-scale climate changes and is marked by stepwise increases in SAR and the ratio of C:N together ...